2017
DOI: 10.4103/jcis.jcis_46_17
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Dual Energy Computed Tomography in Musculoskeletal Imaging

Abstract: The objective of this article is to review the mechanisms, advantages and disadvantages of dual energy computed tomography (DECT) over conventional tomography (CT) in musculoskeletal imaging as DECT provides additional information about tissue composition and artifact reduction. This provides clinical utility in detection of urate crystals, bone marrow edema, reduction of beam hardening metallic artifact, and ligament and tendon analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Streak artifacts changed from more inflow artifacts in aDE, due to the early contrast timing, to more spine artifacts in vDE. We attribute this most likely to be due to an increased beam hardening effect, provoked by the lower main tube voltage (70 kV vs. 80 kV) in the portal venous phase protocol [12,13]. Future protocols could overcome these problems by using a tri-phasic injection protocol on one side and by increasing the tube voltage to 80 or 90 kV on the other [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Streak artifacts changed from more inflow artifacts in aDE, due to the early contrast timing, to more spine artifacts in vDE. We attribute this most likely to be due to an increased beam hardening effect, provoked by the lower main tube voltage (70 kV vs. 80 kV) in the portal venous phase protocol [12,13]. Future protocols could overcome these problems by using a tri-phasic injection protocol on one side and by increasing the tube voltage to 80 or 90 kV on the other [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…4 DECT also offers superior metallic artifact reduction and thus improves in image quality of soft tissue adjacent to metallic implants or devices (e.g., pelvic structure adjacent to metallic hip prosthesis). 5 In clinical practice, DECT is widely used in cardiovascular imaging, especially in evaluating pulmonary thromboembolism and myocardial ischaemia. 6 Other common uses of DECT include the identification of tophi in gouty arthritis and determining renal calculi composition.…”
Section: Introductionmentioning
confidence: 99%
“…6 Other common uses of DECT include the identification of tophi in gouty arthritis and determining renal calculi composition. 5 Studies have demonstrated improvement in detecting and characterization of various renal, adrenal, hepatic, and pancreatic abnormalities. 3 In addition, current dual-energy scanners offer an improved temporal resolution, which is very helpful for CT angiography (CTA), and increased photon flux that improves image quality in large or obese patients.…”
Section: Introductionmentioning
confidence: 99%
“…Resuscitation is also associated with thoracic vertebral trauma [35]. However, CT may not always reveal relevant pathologies or subtle trauma of the spinal ligaments [36].…”
Section: Introductionmentioning
confidence: 99%